India : The Most Dangerous Decades - Harrison, Selig S. (Princeton, NJ : Princeton University Press, 2015)
Mr. Harrison warns that unless a new democratic lender arises when Nehru steps down, India will face Balkanization or authoritarian control based on army force. His disturbing book "is a study of enduring value, fully annotated and indexed and blessed by two of the finest maps in any recent work of scholarship."Originally published in 1960.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Acknowledgments -- Contents -- I. The Politics of National Survival -- II. Past and Future -- III. The New Regional Elites -- IV. The New Caste Lobbies -- V. Indian Communism: The Grand -- VI. Indian Communism: Where Strategy Succeeded -- VII. The Stresses of Indian Politics -- VIII. The Most Dangerous Decades -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Communism -- India; Regionalism -- India; POLITICAL SCIENCE / World / Asian